Demand for Value Added and Value-Added Exchange Rates - Bems, Rudolfs (IMF Working Papers; Working Paper ;, 2015)
We examine the role of cross-border input linkages in governing how international relative price changes influence demand for domestic value added. We define a novel value-added real effective exchange rate (REER), which aggregates bilateral value-added price changes, and link this REER to demand for value added. Input linkages enable countries to gain competitiveness following depreciations by supply chain partners, and hence counterbalance beggar-thy-neighbor effects. Cross-country differences in input linkages also imply that the elasticity of demand for value added is country specific. Using global input-output data, we demonstrate these conceptual insights are quantitatively important and compute historical value-added REERs.